Answer:
The product is positive, thus it is ![\bold{+7a^4b^3}](https://tex.z-dn.net/?f=%5Cbold%7B%2B7a%5E4b%5E3%7D)
Step-by-step explanation:
The full question in proper notation is:
"Find the product. If the result is negative, enter "-". If the result is positive, enter "+".
"
We have to work with it using Order of operations know as well as PEMDAS, thus expression inside parenthesis go first and exponents.
On this expression we have to work with exponents
![(-a^2)^2 = (-a^2)(-a^2) =a^4](https://tex.z-dn.net/?f=%28-a%5E2%29%5E2%20%3D%20%28-a%5E2%29%28-a%5E2%29%20%3Da%5E4)
Thus we get
![-7(-a^2)^2(-b^3)=-7a^4(-b^3)](https://tex.z-dn.net/?f=-7%28-a%5E2%29%5E2%28-b%5E3%29%3D-7a%5E4%28-b%5E3%29)
Lastly we can work with multiplication and remembering that the multiplication of two negative signs becomes positive.
![-7(-a^2)^2(-b^3)=7a^4b^3](https://tex.z-dn.net/?f=-7%28-a%5E2%29%5E2%28-b%5E3%29%3D7a%5E4b%5E3)
So the final simplified expression is ![\bold{7a^4b^3}](https://tex.z-dn.net/?f=%5Cbold%7B7a%5E4b%5E3%7D)
(n + 7)2 = n - 1
2n +14 = n - 1
2n - n +14 = n - n - 1
n + 14 -14 = -1 - 14
n = -15
(-15 + 7)2 = -15 - 1
(-8)2 = -16
-16 = -16
Answer:
![-16x^{2} y^{2}z^{2}](https://tex.z-dn.net/?f=-16x%5E%7B2%7D%20y%5E%7B2%7Dz%5E%7B2%7D)
Step-by-step explanation:
Let's calculate the answer to the second parenthesis. Just multiply throughout to get -8xyz. Then, multiply the first parenthesis by the second. Multiply the constants (-8 and 2) first to get -16, multiply the x's together to get x^2, the y's together to get y^2, and the z's together to get z^2. Put it all together to get
.
M=230
m-80=150
add 80 to each sides